Ambient air levels and atmospheric long-range transport of persistent organochlorines to Signy Island, Antarctica - Kallenborn, Roland; Oehme, Michael; Wynn-Williams, David D; Schlabach, Martin; Harris, Joyce (Science of The Total Environment, 1998)
Levels of persistent organic pollutants (POPs), such as polychlorinated biphenyls and pesticides have been determined in ambient air at Signy Island, Antarctica, over a period of 17 weeks. Mean concentrations for single polychlorinated biphenyls (0.02–17 pg/m3), for chlordanes (0.04–0.9 pg/m3), DDT compounds (0.07–0.40 pg/m3) and γ-hexachlorocyclohexane (HCH, 22 pg/m3) were comparable to those in Arctic air. However, α-HCH levels were approximately one order of magnitude lower. Compared to the Arctic, differences were also observed in the concentration ratios of α-/γ-HCH and chlordane compounds. Two possible atmospheric long-range transport episodes from South America were found by comparing 10-day back trajectories with observed concentration changes. The lower limits of determination (LOD) were mainly governed by the field blanks. They were satisfactory for the most volatile PCBs. However, many concentrations for DDT and chlordane compounds were below the LODs (range 0.1–1 pg/m3) or even the instrumental detection limit (0.01–0.03 pg/m3).
Keywords: Antarktis; atmosfæren; forurensning; langtransport; luftforurensning; meteorologi; miljøgifter; polarområdene

Polychlorinated Dibenzo-p-Dioxins, Dibenzofurans and Coplanar Biphenyls in Antarctic Fur Seal Blubber - Oehme, Michael; Schlabach, Martin; Boyd, Ian (Ambio, 1995)
Levels of polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDF) as well as of coplanar (non-ortho substituted) polychlorinated biphenyls (CB-77, CB-126 and CB-169) have been determined in 11 fur-seal blubber samples from female Antarctic fur seals. Measurable PCDD/PCDF concentrations averaging 2 ppt TEQ (Nordic model) were found. This is considerably less than in Arctic seals. In addition, the PCDD/PCDF congener patterns differed between Antarctic and Arctic seals. The levels of CB-77, CB-126 and CB-169 (8.5-41 pg g-1 for single congeners in average) in Antarctic fur seals were also much lower than in Arctic ringed and harp seals. A possible explanation of these differences is the overall lower environmental pollution of the Southern Hemisphere, though an influence of different age and sex distributions cannot be excluded. The data passed all quality assurance criteria that had been established for such low levels.
Keywords: Antarktis; forurensning; marin biologi; miljøgifter; pinnipedier; polarområdene; seler